1994
DOI: 10.1111/j.1532-5415.1994.tb06217.x
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Case‐Finding Tools for Depression in the Nursing Home: Influence of Clinical and Functional Characteristics and Selection of Optimal Threshold Scores

Abstract: The GDS and BCDRS performed well in the nursing home. As the GDS can serve as a both a case-finding and severity instrument, it is preferred. Use of brief, interviewer-administered tools may improve detection of depression in the nursing home.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
100
1
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(112 citation statements)
references
References 45 publications
10
100
1
1
Order By: Relevance
“…For screening purposes, the Geriatric Depression Scale (GDS) has been shown to be a valid and reliable instrument among institutionalized elderly (Gerety, Williams et al, 1994;McGivney, Mulvihill, & Taylor, 1994;Jongenelis et al, 2005;Lesher, 1986;Yesavage et al, 1983). The GDS was developed to be selfadministered, but in frail nursing home patients it is frequently administered in an interview (Jongenelis et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…For screening purposes, the Geriatric Depression Scale (GDS) has been shown to be a valid and reliable instrument among institutionalized elderly (Gerety, Williams et al, 1994;McGivney, Mulvihill, & Taylor, 1994;Jongenelis et al, 2005;Lesher, 1986;Yesavage et al, 1983). The GDS was developed to be selfadministered, but in frail nursing home patients it is frequently administered in an interview (Jongenelis et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, several efforts have been made to develop self-report screening inventories that would improve the accuracy of detection of depressive symptoms and yet be brief enough for routine administration to the medically ill. Although these measures have generally been found to correlate highly with full-length depression inventories (1)(2)(3)(4), in some cases their concordance with a standard from clinician-administered interviews has been less than optimal (5). Recently, Mahoney et al (6) reported preliminary evidence that a single-item interview for depression was as accurate as the 30-item Geriatric Depression Scale (7) in identifying depressive disorders in older adults.…”
mentioning
confidence: 99%
“…Yesavage et al (1983) introduced the Geriatric Depression Scale, a self-rating, 30 item questionnaire that was especially developed for the elderly, without focusing on physical complaints. This instrument has been found to be reliable and valid in multiple settings, including nursing homes (Yesavage et al, 1983;Lesher, 1986;D'Ath et al, 1994;Gerety et al, 1994;McGivney et al, 1994). On the other hand, it has also been found less feasible for the nursing home setting (Wagenaar et al, 2003).…”
Section: Introductionmentioning
confidence: 99%